Concomitant HPV and MenACWY vaccination among sixth and seventh graders receiving Tdap. Issue 45 (29th October 2018) - Doke, Kaleigh; Fitzgerald, Sharon A.; Barral, Romina L.; Griffin, Phil; Ellerbeck, Edward F.
Highlights: Half of Kansas teens do not receive an HPV or meningococcal vaccine with their Tdap. Most of these children remain unvaccinated 2–3 years later. Concomitant vaccination rates vary by geographic location and insurance type. These vaccines may be more accepted if offered with school-required Tdap vaccines. Abstract: Objective: To describe use of human papilloma virus (HPV) and meningococcal (MenACWY) vaccines among sixth and seventh grade Kansas children receiving their school-required tetanus, diphtheria, and acellular pertussis (Tdap) booster. Methods: We used Medicaid and commercial claims data in Kansas from 2013, 2014, and 2015 to identify HPV and MenACWY vaccinations among sixth and seventh graders receiving a Tdap booster. Rates of concomitant vaccinations were calculated at the state and county level, and logistic regression was used to identify predictors of concomitant vaccination. Results: Of sixth and seventh graders in Kansas receiving their required Tdap booster, 53–82% failed to receive a concomitant HPV vaccine and 36–47% failed to receive a concomitant MenACWY vaccine from 2013 to 2015. Rates of concomitant vaccinations varied more than four-fold across counties. Female gender, younger age, and Medicaid (versus commercial insurance) were positively associated with concomitant vaccination; concomitant vaccination rates increased from 2013 to 2015 (p < 0.001). Of children continuously enrolled in Medicaid from 2013 to 2015, who did not receive concomitant vaccination in 2013, 72.3% and 68.6% remained unvaccinated against HPV and MenACWY, respectively by the end of 2015. Conclusions: Failure to get a concomitant vaccination at the time of their Tdap booster identifies children at high risk of not getting immunized in the ensuing 2–3 years. 'Back to school' programs focusing only on school-required vaccinations could have negative impacts on overall vaccination rates. Tracking rates of concomitant vaccination might be useful in supporting quality assessment and improvement efforts. Clinical trial registration: This study was not a clinical trial.